A newly recorded species \( Strobilanthes lamiifolia\) (Nees) T. Anderson (Acanthaceae) for the flora of Vietnam - Thu Thuy, Nguyen; Hai, Do Van; Thi Hoan, Duong; Lin, Zheli; Deng, Yunfei (Academia Journal of Biology, 2022)
Strobilanthes lamiifolia (Nees) T. Anderson is reported here as a new record for the flora of Vietnam. It is morphologically allied to Strobilanthes sulfurea but differs in the shape of the leaf, bract, and bracteoles. Photographs and line drawings are given together with information on habitat, ecology and preliminary conservation assessment based on IUCN criteria.